Automatic synthesis of multi-agent motion tasks based on LTL specifications - Kyriakopoulos, Kostas J.; Loizou, Savvas (My University, 2004)
In this paper we propose a methodology for automatically synthesizing motion task controllers based on Linear Temporal Logic (LTL) specifications. The proposed design of the underlying multi-agent controllers possess a special structure that allows for implicit satisfaction of basic liveness and safety specifications. The resulting closed loop system is of hybrid nature combining the continuous dynamics of the underlying system with the automatically synthesized switching logic that enforces the LTL specification. The effectiveness of the proposed scheme is verified through non-trivial computer simulations.
Keywords: Computer simulation; Robots; Automation